World Bank Group Support for Small and Medium Enterprises : A Synthesis of Evaluative Findings - Independent Evaluation Group (World Bank, Washington, DC, 2019)
World Bank Group strategy continues to position SMEs as key vehicles to promote employment, value chain development, economic and social inclusion, and resilience in the face of fragility and conflict. This note synthesizes findings regarding SMEs and SME support from recent IEG evaluations, independent evaluations by other MDBs, and relevant World Bank Group research.